Defending Deontic Constraints and Prioritarianism: Two Remarks on Tännsjö’s Setting Health-Care Priorities (Diametros, 2021)
Torbjörn Tännsjö has written a clear and thought-provoking book on healthcare priority setting. He argues that different branches of ethical theory—utilitarianism, egalitarianism, and prioritarianism—are in general agreement on real-world healthcare priorities, and that it is human irrationality that stands in the way of complying with their recommendations. While I am generally sympathetic to the overall project and line of argumentation taken by the book, this paper raises two concerns with Tännsjö’s argument. First, that he is wrong to set aside deontic constraints as irrelevant or as pointing in the same direction as consequentialism. Secondly, that his argument against prioritarianism in favor of utilitarianism is insufficient and under-developed. Given these problems, I conclude that we should welcome Tännsjö’s contribution but with these qualifications in mind.